PLA2G7 associates with hormone receptor negativity in clinical breast cancer samples and regulates epithelial-mesenchymal transition in cultured breast cancer cells - Lehtinen Laura; Vainio Paula; Wikman Harriet; Huhtala Heini; Mueller Volkmar; Kallioniemi Anne; Pantel Klaus; Kronqvist Pauliina; Kallioniemi Olli; Carpen Olli; Iljin Kristiina (Wiley Blackwell, 2022)
Breast cancer is the leading cause of cancer-related deaths in women due to distinct cancer subtypes associated with early recurrence and aggressive metastatic progression. High lipoprotein-associated phospholipase A2 (PLA2G7) expression has previously been associated with aggressive disease and metastasis in prostate cancer. Here, we explore the expression pattern and functional role of PLA2G7 in breast cancer. First, a bioinformatic analysis of genome-wide gene expression data from 970 breast samples was carried out to evaluate the expression pattern of PLA2G7 mRNA in breast cancer. Second, the expression profile of PLA2G7 was studied in 1042 breast cancer samples including 89 matched lymph node metastasis samples using immunohistochemistry. Third, the effect of PLA2G7 silencing on genome-wide gene expression profile was studied and validated in cultured breast cancer cells expressing PLA2G7 at high level. Last, the expression pattern of PLA2G7 mRNA was investigated in 24 nonmalignant tissue samples and 65 primary and 7 metastatic tumour samples derived from various organs using qRT-PCR. The results from clinical breast cancer samples indicated that PLA2G7 is overexpressed in a subset of breast cancer samples compared to its expression in benign breast tissue samples and that high PLA2G7 expression associated with hormone receptor negativity as well as with poor prognosis in a subset of breast cancer samples. In vitro functional studies highlighted the putative role of PLA2G7 in the regulation of epithelial-mesenchymal transition (EMT)-related signalling pathways, vimentin and E-cadherin protein expression as well as cell migration in cultured breast cancer cells. Furthermore, supporting the findings in breast and prostate cancer, high PLA2G7 mRNA expression was associated with metastatic cancer in four additional organs of origin. In conclusion, our results indicate that PLA2G7 is highly expressed in a subset of metastatic and aggressive breast cancers and in metastatic samples of various tissues of origin and promotes EMT and migration in cultured breast cancer cells.